Poetics of Narrative in Antoine Volodine’s Novels - Victoriya Chub (Pitannâ Lìteraturoznavstva)
Antoine Volodine is reputed for inventing new forms in the French literature at the turn of XX–XXI centuries. Our study is dedicated to Volodine’s narrative structure, i.e. the stratification of narrative instances, the depersonalization of narrator and characters, the metanarrativization of story. Antoine Volodine creates a fictional world of uncertain characters floating between life and death and telling their stories in polyphonic voices. First, our study revealed the lack of demarcation between “I” and “we” and the blend of narrative levels created by ambivalent voices merging into a single “post-exotic horn”. Second, we discovered that metatextual comments and narrative figures of “mise en abyme” and metalepsis help to “alienate” the text and dramatize the relations between the author and readers. As a result, a specific “textual fiction” is being created to embody philosophical problems in Volodine’s meta-utopic novels. Finally, the research determined a set of poetical dominants typical for Volodine’s novels: the interference of homo- and heterodiegetic narrator instances, the uncertain nature of narrators and characters, the polyphonic character of voices as well as metatextual and transgressive structures. It was concluded that the revealed poetical dominants are not only a part of the literary game, but a specific way to represent the speech act. Antoine Volodine’s multilevel narrators share common mental pictures that show the experience of defeat, marginalization and imprisonment. The specific narrative structure helps the writer to create the effect of ambiguity and vagueness, adds a bit of doubt in the act of perception of his novels, updates the metaphysical perspective of the postmodern anti-utopia.